Temporo-spectral imaging of intrinsic optical signals during hypoxia-induced spreading depression-like depolarization. - Maria Mané (PLoS ONE, 2012)
Spreading depression (SD) is characterized by a sustained near-complete depolarization of neurons, a massive depolarization of glia, and a negative deflection of the extracellular DC potential. These electrophysiological signs are accompanied by an intrinsic optical signal (IOS) which arises from changes in light scattering and absorption. Even though the underlying mechanisms are unclear, the IOS serves as non-invasive tool to define the spatiotemporal dynamics of SD in brain slices. Usually the tissue is illuminated by white light, and light reflectance or transmittance is monitored. Using a polychromatic, fast-switchable light source we now performed temporo-spectral recordings of the IOS associated with hypoxia-induced SD-like depolarization (HSD) in rat hippocampal slices kept in an interface recording chamber. Recording full illumination spectra (320-680 nm) yielded distinct reflectance profiles for the different phases of HSD. Early during hypoxia tissue reflectance decreased within almost the entire spectrum due to cell swelling. HSD was accompanied by a reversible reflectance increase being most pronounced at 400 nm and 460 nm. At 440 nm massive porphyrin absorption (Soret band) was detected. Hypotonic solutions, Ca(2+)-withdrawal and glial poisoning intensified the reflectance increase during HSD, whereas hypertonic solutions dampened it. Replacement of Cl(-) inverted the reflectance increase. Inducing HSD by cyanide distorted the IOS and reflectance at 340-400 nm increased irreversibly. The pronounced changes at short wavelengths (380 nm, 460 nm) and their cyanide sensitivity suggest that block of mitochondrial metabolism contributes to the IOS during HSD. For stable and reliable IOS recordings during HSD wavelengths of 460-560 nm are recommended.